2009
DOI: 10.1128/mcb.01740-08
|View full text |Cite
|
Sign up to set email alerts
|

Normal Function of the Yeast TOR Pathway Requires the Type 2C Protein Phosphatase Ptc1

Abstract: Yeast ptc1 mutants are rapamycin and caffeine sensitive, suggesting a functional connection between Ptc1 and the TOR pathway that is not shared by most members of the type 2C phosphatase family. Genome-wide profiling revealed that the ptc1 mutation largely attenuates the transcriptional response to rapamycin. The lack of Ptc1 significantly prevents the nuclear translocation of Gln3 and Msn2 transcription factors to the nucleus, as well as the dephosphorylation of the Npr1 kinase, in response to rapamycin. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 78 publications
5
47
0
1
Order By: Relevance
“…In this regard, it has been recently shown that Ptc1 is required for normal TOR signaling, possibly by regulating a step upstream of the type 2A-related Ser/Thr phosphatase Sit4 in a way independent of the HOG pathway (28). This finding provides the first evidence that a PP2C is linked to this important and conserved pathway.…”
supporting
confidence: 51%
“…In this regard, it has been recently shown that Ptc1 is required for normal TOR signaling, possibly by regulating a step upstream of the type 2A-related Ser/Thr phosphatase Sit4 in a way independent of the HOG pathway (28). This finding provides the first evidence that a PP2C is linked to this important and conserved pathway.…”
supporting
confidence: 51%
“…This induction is decreased in the ptc1 mutant (Gonzalez et al 2009) (Figure S1). We tested, by using transcriptional fusions of the promoters to the lacZ reporter gene, whether further deletion of MKK1 or MKK2 would rescue normal gene expression.…”
Section: Resultsmentioning
confidence: 98%
“…Cells carrying plasmids pGAP1 and pMEP1 (Gonzalez et al 2009), pKC201 (Alepuz et al 1997), pMLP1-LacZ (Garcia et al 2009), and pAMS366 (Stathopoulos and Cyert 1997) were grown to saturation on synthetic medium lacking uracil or, in the case of pMEP2 (Marini et al 1997), lacking leucine and then inoculated into 5 ml of YPD medium up to an OD 660 of 0.2. Growth was resumed until an OD 660 of 0.8 was reached.…”
Section: B-galactosidase Reporter Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…On a poor N source or in the presence of rapamycin, conditions of low TORC1 activity, Npr1 is weakly phosphorylated and active, whereas in the presence of amino acids, TORC1 is stimulated and promotes Npr1 hyperphosphorylation, causing its inactivation (19,63). Hyperphosphorylation of Npr1 is also observed in mutant cells lacking the TORC1-regulated protein phosphatase 2A (PP2A)-related phosphatase Sit4 (32) or the Ptc1 PP2C phosphatase controlling Sit4 (20). The current model (Fig.…”
mentioning
confidence: 99%